PELAKSANAAN PEMBELAJARAN BAHASA INDONESIA BERBASIS TEKS DI KELAS XI SMA NEGERI 3 PONTIANAK - Hariantino, Hariantino; Abdussamad, Abdussamad; Ramdani, Deden (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was motivated by the researcherâ€™s desire to identify the process of Indonesia Language subject implementation text based that has been done by the teacher. The method of research in this study is descriptive method qualitative as the form of this study. The data sources in this study are the teacher and the students. The technique of data collections are using observation technique, interview and documentation. The tools of data collection is observation guidelines (APKG), recording sheet, and documentation tools. The result of this study is a lesson plan (RPP) arranged by the teacher had described there was an activity in learning Indonesia language text based and already meet the criteria in Pemendikbud Number 22 Year 2016 about the standard of process Dikdasmen. Implementation of learning which implemented by the teacher was already appropriate to RPP, it showed there was an activities in learning text based, and it had met criteria in Pemendikbud Number 22 Year 2016 about the Standard of Process Dikdasmen. Evaluation that had been done by the teacher already appropriate to an evaluation to learning Indonesia language text based and already met criteria in Pemendikbud Number 22 Year 2016 about the Standard of Process Dikdasmen.Â Â Keywords: Text-Based Indonesian Language Learnin